Headteacher change leadership competency: a study in Malaysian primary schools - Tai, Mei Kin; Abdull Kareem, Omar (Professional development in education, 2020)
The main aim of the study was to examine whether headteachers in Malaysian primary schools were equipped with the relevant competencies to execute school change, in the light of increasing demands for educational excellence and ensuing school reforms. A comparison was made between the National School (NS) and National-Type Chinese School (NTCS). Data were analysed based on 1776 responses from headteachers, senior assistants and teachers. The finding showed that headteachers of NS and NTCS were found competent in change leadership competency (CLC). They were found competent in Goal Framing, Capacity Building and Institutionalizing but less competent in Defusing Resistance and Conflict. Comparatively, headteachers of NS were found more competent than headteachers of NTCS in every domain of CLC and the differences were significant. Three important observations were found in the current study: (i) the incidence of headteachers being exposed to professional development programmes accounts for a significant variation in participant competence; (ii) professional development programmes must be specifically targeted to the distinct needs of the leaders if it is to be effective; and (iii) any examination of change resistance and conflict must start with the human factor as the most potent leverage for sustainable change resides within the human system.